2019
DOI: 10.1103/physrevd.100.114033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interpretation of the Pc(4440) and Pc(4457) sta

Abstract: A molecular model of the P c ð4457Þ and P c ð4440Þ LHCb states is proposed. The model relies on channels coupled by long-range pion-exchange dynamics with features that depend crucially on the novel addition of the Λ c ð2595ÞD channel. A striking prediction of the model is the unusual combination of quantum numbers J P ð4457Þ ¼ 1=2 þ and J P ð4440Þ ¼ 3=2 −. Unlike in other models, a simultaneous description of both states is achieved without introducing additional short-range interactions. The model also gives… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 75 publications
3
61
1
Order By: Relevance
“…[51] the likely existence of two peaks is proposed for the P c ð4457Þ state with J P ¼ 1 2 AE , whenDΛ c ð2595Þ is taken into account for its close threshold as first introduced and studied in Refs. [62,63]. By contrast, using the S-matrix approach and performing a systematic analysis of the reaction amplitudes, Fernández-Ramírez et al [64] explained P c ð4312Þ as a virtual state.…”
Section: Introductionmentioning
confidence: 99%
“…[51] the likely existence of two peaks is proposed for the P c ð4457Þ state with J P ¼ 1 2 AE , whenDΛ c ð2595Þ is taken into account for its close threshold as first introduced and studied in Refs. [62,63]. By contrast, using the S-matrix approach and performing a systematic analysis of the reaction amplitudes, Fernández-Ramírez et al [64] explained P c ð4312Þ as a virtual state.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that P c ð4312Þ is located 9.8 MeV below theDΣ c threshold, and P c ð4440Þ and P c ð4457Þ are 21.8 and 4.8 MeV below theD Ã Σ c one, they provide the most robust candidates so far for hadronic molecules. 1 Indeed, a large number of theoretical works have been performed within the molecular picture, focusing on various aspects ranging from mass spectroscopy [26][27][28][29][30][31][32][33][34][35][36][37][38][39] and decay widths [40][41][42][43][44][45] to production mechanisms [46][47][48][49][50]. In our previous work, we adopted the contact range effective field theory (EFT) to describe the three pentaquark states in the hadronic molecular picture, and we showed the emergence of a complete multiplet of hadronic molecules in the meson-baryon system [26], dictated by heavy quark spin symmetry (HQSS) [51,52], which has later been corroborated by many studies [26,30,32,33,35,53].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [13] it is shown that the usual molecular scenarios cannot explain the production rate of P c states in Λ b decays. Moreover, the paper points out the need to couple the Σ + c D * 0 and the Λ c (2595)D channels due to the very close proximity of their thresholds.…”
Section: Introductionmentioning
confidence: 99%